Justifications of Copyright and Changes of Technological Paradigms - Jovanović, Nikola (65 pravne znanosti v Mariboru, 2026)
This chapter analyzes the evolution of copyright law as an ongoing dialogue between technological innovation and the pragmatic interests of stakeholders, spanning from its origins to the digital reforms of the late 20th century. It focuses on the dualism between the continental droit d’auteur system, which views copyright as an emanation of the author’s personality, and the common law copyright system, based on the utilitarian promotion of knowledge development and dissemination. The author discusses contemporary challenges posed by generative artificial intelligence, which calls into question several fundamental and traditional copyright institutes. Considering these shifts, the chapter emphasizes the necessity of returning to the field’s philosophical and historical foundations. Only by re-evaluating core theoretical justifications can an appropriate legal response be formulated to the transformation caused by AI, thereby preserving the integrity of copyright law in the digital age.